2009
DOI: 10.1128/jvi.00241-09
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Vaccines for H5N1 Influenza Virus in Ferrets Reveals the Potential for Protective Single-Shot Immunization

Abstract: As part of influenza pandemic preparedness, policy decisions need to be made about how best to utilize vaccines once they are manufactured. Since H5N1 avian influenza virus has the potential to initiate the next human pandemic, isolates of this subtype have been used for the production and testing of prepandemic vaccines. Clinical trials of such vaccines indicate that two injections of preparations containing adjuvant will be required to induce protective immunity. However, this is a working assumption based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 25 publications
5
50
2
Order By: Relevance
“…We have shown that one submicrogram injection of rH5 produced in insect cells is effective in protecting mice and ferrets against lethal H5N1. These findings surpass other preclinical H5N1 vaccine studies (31,32) and predict that this protein will be an important antigen for human use. Our studies also highlight the attributes of GLA-SE in stimulating single-dose protection against a poorly immunogenic virus.…”
Section: Discussioncontrasting
confidence: 39%
“…We have shown that one submicrogram injection of rH5 produced in insect cells is effective in protecting mice and ferrets against lethal H5N1. These findings surpass other preclinical H5N1 vaccine studies (31,32) and predict that this protein will be an important antigen for human use. Our studies also highlight the attributes of GLA-SE in stimulating single-dose protection against a poorly immunogenic virus.…”
Section: Discussioncontrasting
confidence: 39%
“…Our own studies in the ferret provided an indication that in the event of a future influenza pandemic, effective mass vaccination may be achievable with a low-dose "single-shot" vaccine including AlPO 4 or ISCOMATRIX ® adjuvant. 58 While the data from these studies is encouraging at present, the precision with which the ferret influenza model correlates with humans remains unknown.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 96%
“…When comparing prototype vaccines in the ferret model, we have recently shown that inclusion of AlPO 4 or ISCOMATRIX ® adjuvant significantly reduced the level of virus isolated from nasal washes with a concomitant reduction in disease severity. 58 virus could achieve in clinical studies what would be considered to be sufficient responses to be protective. [39][40][41][42][43][44][45][46][47][48][49] Meta-analysis of the results with different prototype vaccines suggested that low doses (<10 µg of antigen) in combination with non-aluminiumbased adjuvants induced robust antibody responses that were in the range acceptable for the licensing of seasonal vaccines in the European Union.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports on H5N1 vaccine studies in ferrets have indicated at least some HI titer response when adjuvant is present. 18,20,21 Since 100% protection was achieved in several of the groups in the current study, alternative immunological mechanisms may function in protection in ferrets, such as CD4C T-cell responses 22 or antibody (non-HI antibody) dependent cytotoxicity (ADCC) responses. 23 In ferrets, influenza virus infection of the central nervous system (CNS) is particularly common with highly pathogenic A influenza H5N1 viruses.…”
Section: Discussionmentioning
confidence: 99%